Microbiological evaluation of sugarcane juice sold at street stands and juice handling conditions in São Carlos, São Paulo, Brazil - Aline Cristine Garcia Oliveira; Antonio Sergio Spano Seixas; Cristina Paiva Sousa; Clovis Wesley Oliveira Souza (Cadernos de Saúde Pública)
Fresh sugarcane juice is sold by street vendors without any heat treatment in São Carlos, São Paulo, Brazil. Twenty-four samples of point-of-sale juice were tested by standard methods to determine heterotrophic bacteria, total and thermo-tolerant coliform counts, Salmonella, and parasites in the juice. 25% of samples showed poor sanitary conditions, with thermo-tolerant coliform levels higher than allowed by Brazilian standards. Salmonella spp. and parasites were absent in all samples. Thermo-tolerant coliforms were detected on the hands of 37% of juice handlers, and heterotrophic bacterial counts reached 2.0 x 10³ cfu/per hand. Escherichia coli was detected in one hand sample, and no Salmonella spp. was detected. Screening questionnaires were used to interview the vendors, and 62% of interviewees were either unfamiliar with or failed to adopt adequate hygiene for food handling.